2011
DOI: 10.1002/cphc.201100154
|View full text |Cite
|
Sign up to set email alerts
|

Effect of PIP2 on Bilayer Structure and Phase Behavior of DOPC: An X‐ray Scattering Study

Abstract: Phosphatidylinositol 4,5-bis-phosphate (PIP(2)) is an important lipid in regulation of several cellular processes, particularly membrane fusion. We use X-ray diffraction from solid-supported multilamellar 1,2-dioleoyl-sn-glycero-3-phosphocholine (DOPC)/PIP(2) samples to study changes in bilayer structure and the lyotropic phase behavior induced by physiologically relevant concentrations of PIP(2) . Electron-density profiles reconstructed from X-ray reflectivity measurements indicate that PIP(2) strongly affect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 49 publications
2
26
0
Order By: Relevance
“…With additional control parameters (i.e., osmotic pressure, temperatature, composition) a transition to a nonlamellar states is then easily induced. In this context, we also found that the lipid phosphatidylinositol-4,5-bisphosphate (PIP 2 ), which is enriched at the sites of vesicle fusion of synaptic membranes (84,85), has a very pronounced effect on the phase behavior of DOPC and promotes stalk and inverted hexagonal phase formation already at concentrations of few mol% (43). As a strongly anionic lipid with three net negative charges, PIP 2 is likely to interact with Ca 2þ , possibly again facilitating localized dehydration and hydrophobic defect formation.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…With additional control parameters (i.e., osmotic pressure, temperatature, composition) a transition to a nonlamellar states is then easily induced. In this context, we also found that the lipid phosphatidylinositol-4,5-bisphosphate (PIP 2 ), which is enriched at the sites of vesicle fusion of synaptic membranes (84,85), has a very pronounced effect on the phase behavior of DOPC and promotes stalk and inverted hexagonal phase formation already at concentrations of few mol% (43). As a strongly anionic lipid with three net negative charges, PIP 2 is likely to interact with Ca 2þ , possibly again facilitating localized dehydration and hydrophobic defect formation.…”
Section: Discussionmentioning
confidence: 90%
“…2B) were then reconstructed by aid of the swelling method for lamellar phases described e.g., in ref. 43 and references therein. Following the well established osmotic stress method (31,33,42), it is assumed that the total attractive pressure can be approximated by the osmotic pressure P ¼ −ðk B T ∕v w Þ lnðRH∕100%Þ which dominates the van der Waals attraction in the used RH range (33,88).…”
Section: Methodsmentioning
confidence: 99%
“…1,35,37 The applied protocols are described elsewhere in detail. 21,38,39 In brief, stacks of about 1500 aligned lipid bilayers were prepared on silicon substrates and placed in an environmental chamber with precise RH control. 39 The latter allowed us to tune the osmotic pressure .…”
Section: X-ray Reectivity Measurementsmentioning
confidence: 99%
“…ref. 38 and 41 and references therein) as follows: rstly, due to the nonmonotonous curve d(RH), only data for RH > 85% in the regime of "normal" swelling were used (Fig. 1b).…”
Section: X-ray Reectivity Measurementsmentioning
confidence: 99%
“…According to molecular dynamics (MD) simulations, PIP 2 changes the structural properties of the host lipid bilayer by rearranging and reorganizing its surrounding lipids to form stable microdomains [31]. The phase diagram of PC/PIP 2 shows that it can promote non-lamellar phases [14]. At low concentration, PIP 2 promotes the stalk-phase, and at higher concentration the formation of the hexagonal phase, which is usually not observed for pure DOPC.…”
Section: Introductionmentioning
confidence: 99%